Alopecia Totalis in a Five-Year-Old Boy: A Case Report - Ringoringo, Harapan Parlindungan (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Alopecia totalis (AT) represent the severe form of alopecia areata with a worse prognosis. In population the prevalences of alopecia totalis, is 0,08%. This study shows that Prosential, minoxidil 2% and clobetasol propionate 0.05% therapy for hair loss could be considered Case presentation: A 5-year-old boy weighing 13.4 kg came to the hospital complaining of hair loss all over his head, bald since two months before. The eyebrows, eyelashes, and nose hairs were also missing. The diagnosis is alopecia totalis. The patient was given Prosential therapy for four months. After two months of treatment, hair started to grow slightly, evenly across the head, eyebrows, and eyelashes. After that, the patient was lost contact. 4 months later, the patient returned with hair loss complaints again.The patient’s vital signs are normal. Eyes, ENT, heart, lungs, abdomen: normal. Skin: no hair. Laboratorium: Hemoglobin 12.1 g/dL, leukocytes 6,480/uL, platelets 324,000/uL, hematocrit 35.5%, Diff Count: basophils 0%, eosinophils 22%, stems 1%, segments 27%, lymphocytes 41%, monocytes 9%. Feces and urine analysis were normal. Glucose 86 mg/dL, total cholesterol 128 mg/dL, triglycerides 46 mg/dL. Albumin 4.33 g/dL, globulin 1.41 g/dL. Uric acid 4.64 mg/dL. Kidney and liver function were normal. Thyroid function: FT4: 1.1 ng/dL, TsHs 0.916 uIU/mL. The ANA test was negative. Diagnosis: Idiopathic alopecia totalis with hypereosinophilia. The therapy was Prosential, minoxidil 2% and clobetasol propionate 0.05%. Conclusion: The etiology of AT should be sought in as much detail as possible because alopecia management requires a holistic approach, including psychosocial support. Hair loss is a significant factor affecting the self-esteem of children.